1999
DOI: 10.3354/meps176153
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic acid depuration in the mussel Mytilus galloprovincialis:one- and two-compartment models and the effect of environmental conditions

Abstract: Following a n episode of Diarrhetic Shellfish Poisoning (DSP) in mussels Mytilus galloprovincialis from the Ria d e Pontevedra (Galicia, IWV Spain), produced by organisms of the genus Dinophysis [dinoflagellate), a batch of contaminated mussels was transplanted to several uncontaminated sites having different environmental condit~ons. The depuration kinetics of o k a d a~c acid (the dominant toxin involved in the episode) in each experimental mussel batch was monitored during a 70 d period, as were the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 12 publications
3
27
1
5
Order By: Relevance
“…population had declined and the toxicity in the plankton community again was very low. It has been suggested in several papers that the main factor affecting the rate of depuration of DST in mussels is the quantity of non-toxic food available for mussels to feed upon (Haamer et al 1990b, Sampayo et al 1990, MarcaillouLe Baut et al 1993, Poletti et al 1996, Blanco et al 1999. In this study, the low chl a observed in the water after the Dinophysis spp.…”
Section: Discussionmentioning
confidence: 54%
“…population had declined and the toxicity in the plankton community again was very low. It has been suggested in several papers that the main factor affecting the rate of depuration of DST in mussels is the quantity of non-toxic food available for mussels to feed upon (Haamer et al 1990b, Sampayo et al 1990, MarcaillouLe Baut et al 1993, Poletti et al 1996, Blanco et al 1999. In this study, the low chl a observed in the water after the Dinophysis spp.…”
Section: Discussionmentioning
confidence: 54%
“…Mussel size has previously been speculated (but not proven) to be negatively correlated with toxin depuration rate (Duinker et al, 2007). The depuration rates in the present study cover only the first few days of depuration, and if there is both a labile and a more slowly depurated toxin pool as suggested by Blanco et al (1999) and Moroño et al (2003), then our one-compartment model could overestimate the depuration rates.…”
Section: Depurationmentioning
confidence: 54%
“…Depuration (or detoxification) has been studied more intensely using mussels contaminated in situ. Effects of various parameters, including food availability (Blanco et al, 1999;Svensson, 2003;Svensson and F€ orlin, 2004;Marcaillou et al, 2010), temperature (Shumway and Cembella, 1993;Blanco et al, 1999) and mussel size and lipid content (Svensson and F€ orlin, 2004;Duinker et al, 2007) have been evaluated using different mussel species. Reported toxin half-life times vary substantially, from less than a day to 25 days, but despite the efforts, depuration kinetics of DSP toxins is far from well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This apparent "over contamination" at an early stage of the decontamination has been already described (Marcaillou et al 1993;Blanco et al 1999). In a review, Blanco et al (2005) proposed a model describing the evolution of OA and its derivatives over the course of decontamination.…”
Section: Discussionmentioning
confidence: 78%